Surfacing the ‘silent foundation’: which information behaviour theories are relevant to public library reference service? - Amy VanScoy; Africa S. Hands; Katarina Švab; Tanja Merčun (Information Research: An International Electronic Journal)
Introduction. Despite extensive discussions on the theory/practice gap in library and information science, there is a paucity of research on the value and use of formal theory by librarians in their daily practice.